[PP.19.04] SLEEP HISTORY AND HYPERTENSION BURDEN IN FIRST GENERATION CHINESE MIGRANTS SETTLED IN THE SOUTH OF EUROPE; THE CHINESE IN PRATO CROSS-SECTIONAL SURVEY. (September 2016) - Modesti, P.A.; Perruolo, E.; Calabrese, M.; Bussotti, A.; Malandrino, D.; Zhao, D.
Abstract : Objective: Migration flows from China are largely directed towards the South of Europe, Chinese being now the third largest overseas-born population in Italy. Social conditions and working pressure might influence sleep history of first generation Chinese migrant workers with a final potential influence on risk factors. Little research has however been carried out on the relationship between sleep history and hypertension in first generation Chinese migrants. The aim of the study was to investigate the relationship between hypertension burden and self-reported sleep disorders among Chinese migrants settled in Prato. Design and method: Cross-sectional survey. A sample of first-generation Chinese migrants aged 16–59 years, and living in Prato was recruited in a cross sectional survey. Blood pressure values were measured with validated devices and hypertension was defined according to ESH guidelines; hypertension prevalence was based on direct standardization using the 2001 WHO World Standard Population; potential impact of self-reported sleep disorders was analysed by logistic regression adjusted for main demographic, antropometric, socio-economic, and health related confounders. Results: Among the 1608 participants, 21.7% were hypertensive (age-standardized prevalence 19.2%; 95% Cl 18.5 to 20.0); 54% of hypertensive subjects were aware of their condition; 70% of aware hypertensive subjects received drugs, and 39% of treated subjects had blood pressure controlled. Self-reported snoring increased the risk of hypertension; when compared with no snoring, the age- and sex-adjusted OR for hypertension of snoring 3–6 d/week was 2.11 (95% Cl 1.48 to 3.01), and 2.48 (95% Cl 1.79 to 3.46) of snoring every day. When compared with a sleep duration of 5 hours or less, subjects with sleep duration of 7 hours had reduced risk of high triglycerides (adjusted OR 0.64; 95% Cl 0.43 to 0.95). Figure. No caption available. Conclusions: The limited information available on Chinese communities living in Europe highlights the strength of the present study. Despite an high level of awareness, low treatment rates for hypertension were observed among Chinese participants, independently from health insurance. Sleep history is to be considered in screening and prevention programs.